Social and Human Development in Vietnam - Nguyen, Vu Hao; Briesen, Detlef (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
In the Global South, especially in countries like Vietnam, enormous economic growth has taken place over the last 40 years, and society has changed extensively. Today, there is an intense, multifaceted debate about this and about further social and human development: It is based on traditional Western and Eastern schools of thought and their reassessment as well as on the UN's 17 SDGs or on experiences with concrete policies for the economy, society and the environment. This book documents this debate focusing on the international dimension, social and human development as well as on corresponding case studies, and particularly in relation to the diverse traditions of the country.With contributions byDo Hoang Anh | Ha Thi Bac | Detlef Briesen | Nguyen Thị Kim Chi | Nguyen Ngoc Diep | Nguyen Hoang Duc | Jean-François Dupeyron | Pham Hoang Giang | Pham Thanh Ha | Luong Dinh Hai | Nguyen Vu Hao | Truong Thi Quynh Hoa | Nguyen Quynh Huong | Nguyen Thanh Huong | Do Thi Thanh Huyen | Lai Quoc Khanh | Dang Thi Lan | Nguyen Thi Lien | Nguyen Thi Chau Loan | Winfried Löffler | Phan Thanh Nham | Nguyen Thi Nhu | Nguyen Viet Phuong | Nguyen Minh Quang | Ly Luong Son | Mai Thi Thanh | Nguyen Thi Kim Thanh | Le Thi Trang | Nguyen Anh Tuan | Nguyen Thi Thuy Van | Le Thi Vinh